2016
DOI: 10.5539/ies.v9n5p115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core Training Program on Physical Functional Performance in Female Soccer Players

Abstract: <p class="apa">The purpose of this study was to determine the effect of core training program on speed, acceleration, vertical jump, and standing long jump in female soccer players. A total of 40 female soccer players volunteered to participate in this study. They were divided randomly into 1 of 2 groups: core training group (CTG; n = 20) and control group (CG; n = 20). The mean (SD) age was 19.05 ± 1.15 years, height was 160.60 ± 4.22 cm, weight was 56.45 ± 3.33 kg, and sport age was 4.50 ± 1.24 for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 13 publications
0
22
0
1
Order By: Relevance
“…Additionally, there was significant variation in the dribbling and passing skills from among football technical skills for players participating in strength training, with significant development in terms of dribbling skills of players with strength training compared to those without strength training. It is commonly reported in previous studies that different resistance training types have positive effects on the motor skills of footballers like speed (Brito et al 2014,Meylan and Malatesta 2009, Christou et al2006, strength (Brito et al 2014, Jay et al 2004, Christou et al2006, quickness (Meylan andMalatesta 2009, Christou et al2006), stamina (Helgerud et al 2001) and balance (Iacono et al 2016, Sever 2017, Taskin 2016, Yıldızer and Kirazci 2017. Contrary to this, when the limited studies investigating the effect of this type of training on the technical skills of footballers are examined, it was found that speed and jumping work applied during the season had a positive effect on kicking skills of footballers (marques et al 2013, Sedano et al 2009, Villarreal et al 2015, Haghighi et al 2012, Manolopoulos et al 2004.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, there was significant variation in the dribbling and passing skills from among football technical skills for players participating in strength training, with significant development in terms of dribbling skills of players with strength training compared to those without strength training. It is commonly reported in previous studies that different resistance training types have positive effects on the motor skills of footballers like speed (Brito et al 2014,Meylan and Malatesta 2009, Christou et al2006, strength (Brito et al 2014, Jay et al 2004, Christou et al2006, quickness (Meylan andMalatesta 2009, Christou et al2006), stamina (Helgerud et al 2001) and balance (Iacono et al 2016, Sever 2017, Taskin 2016, Yıldızer and Kirazci 2017. Contrary to this, when the limited studies investigating the effect of this type of training on the technical skills of footballers are examined, it was found that speed and jumping work applied during the season had a positive effect on kicking skills of footballers (marques et al 2013, Sedano et al 2009, Villarreal et al 2015, Haghighi et al 2012, Manolopoulos et al 2004.…”
Section: Discussionmentioning
confidence: 96%
“…They also stated that the core training program applied in addition to football training made significant contributions to agility and sprint performance. Similarly, Taskin (2016) has showed that sprint, acceleration and vertical jump performances were improved in core exercises performed for 8 weeks, 3 days a week. For this reason, a similar study, which states that core training is required for optimal performance in all sports branches, emphasized that it has positive results in 10 and 20 meter sprint performances (Prieska et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…Apart from physical performance, even healthy individuals need to develop a strong and stable core to help prevent injury and improve athletic performance (Riera, 2017). Core exercises have positive effects on core muscles and especially strength development (Taskin, 2016). The lower extremity and core region muscle strength is an important element for success in many competitions and sports branches for optimal performance (Axel at al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Esta habilidad puede ser entrenada para realizar ejercicio terapéutico, prevención de lesiones y aumento del rendimiento deportivo haciendo énfasis en la progresión de ejercicios basados en control motor a nivel estático y dinámico especifico de este tipo de musculatura (75,(79)(80)(81). En el deporte de alto rendimiento, permite estabilizar el tronco y pelvis mediante la corrección de la técnica de ejecución, funciona como un transmisor de fuerza entre los miembros superiores e inferiores y desarrollar un mejor movimiento funcional mediante la aplicación de estímulos mediante rotaciones en posición supina, prona, lateral, isometría, trabajos con peso y con elementos adicionales que generan adaptaciones en los deportistas y mejoran el rendimiento físico y habilidades especificas (16,75,78,(82)(83)(84)(85)(86).…”
Section: Coreunclassified